Synthesis of Vinylsulfone Based Poly Anchor Reactive Dyes and their Applications on Cotton Fabric - Ahmad, B.; Bhatti, I.A.; Bhatti, H.N.; Hussain, M.T.; Abbas, M.; Shahid, M. (Asian Journal of Chemistry, 2013)
Three vinylsulfone based poly anchor reactive dyes have been synthesized by following condensation, diazotization and coupling reactions respectively, with a view to achieve bright shades and good fastness properties. Cotton fabric was desized, bleached and mercerized before dyeing and application studies. Pad-thermosol dyeing method was employed since it is more environment friendly due to high dye fixation. Effect of different dyeing parameters i.e. salt concentration, dyeing time, dyeing temperature and pH of dye solution were optimized. The dyed fabrics were subjected to CIE LAB and LCH system in order to evaluate the dyeing quality parameters by using Spectraflash SF-600 at Noor Fatima Textile Pvt. Ltd., Faisalabad. Fastness properties such as perspiration, light, washing, chlorinated water, dry cleaning and crocking were evaluated for the dyed fabrics by following ISO standard test methods.